Modeling and Simulation of Static Strength Railway Bogie Bolster Using Ansys Workbench - Wirawan, Willy; Zulkarnain, Akbar; Satrio Utomo, Ilham; Sabilil Rouf, Muhammad; Aizuddin Bin Azari, Muhammad; Prasetijo, Joewone (Nusantara Publisher, 2024)
This study aimed to ensure that plastic deformation does not occur on the structure of bolster bogie 1722 when it accommodates burdens or loads based on previously determined overload limit. The simulation in this study used the finite element method with the help of Ansys Workbench 2020. The standard of testing UIC 515-4 was employed as a reference for the simulation, notably in determining the load case. The result of static simulation on the overload showed that the maximum stress on the vertical load case was 72.764 MPa, and the maximum stress on the transverse and vertical load case (combination) was 109.9 MPa. The result of maximum vertical deflection was obtained from the case of vertical load as 0.553 mm and in the case of transverse and vertical load (combination) as 1.799 mm. The structure of the bolster design is considered safe because the maximum score of stress was under the yield strength score of the used material, namely SS400 as 245 Mpa.